2014
DOI: 10.1002/eqe.2455
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional behavior of unreinforced masonry walls

Abstract: SUMMARYMost of the studies related to the modeling of masonry structures have by far investigated either the in-plane (IP) or the out-of-plane (OP) behavior of walls. However, seismic loads mostly impose simultaneous IP and OP demands on load-bearing or shear masonry walls. Thus, there is a need to reconsider design equations of unreinforced masonry walls by taking into account bidirectional effects. The intent of this study is to investigate the bidirectional behavior of an unreinforced masonry wall with a ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
0
13
0
2
Order By: Relevance
“…This model has been improved with the introduction of a routine that removes from the structural model the elements representative of the infill when their IP-OOP displacement history exceeds the interaction domain in ultimate displacements. 54 In 2014, Dolatshahi et al 55 carried out three-dimensional FEM analyses resulting in interaction domains in yielding and peak load represented by elliptical yielding curves. In this model, the infill is represented by four diagonal rigid elements joined in the center by one element, which takes into account the nonlinearity of the infill behavior.…”
Section: Infills' Modeling Accounting For the In-plane/out-of-planementioning
confidence: 99%
“…This model has been improved with the introduction of a routine that removes from the structural model the elements representative of the infill when their IP-OOP displacement history exceeds the interaction domain in ultimate displacements. 54 In 2014, Dolatshahi et al 55 carried out three-dimensional FEM analyses resulting in interaction domains in yielding and peak load represented by elliptical yielding curves. In this model, the infill is represented by four diagonal rigid elements joined in the center by one element, which takes into account the nonlinearity of the infill behavior.…”
Section: Infills' Modeling Accounting For the In-plane/out-of-planementioning
confidence: 99%
“…In another work by Dolatshahi et al . , IP–OP interaction of a URM wall with a typical aspect ratio under different monotonic and cyclic loading protocols was examined. The results indicate that the direction of the resultant force of the wall is initially proportional to the ratio of stiffness in the IP and the OP directions.…”
Section: Introductionmentioning
confidence: 99%
“…19 against the normalized IP load which is the IP force at each considered IP displacement demand level (FME, SME or TME) normalized to the IP force capacity (at SME). For comparison purposes, the results of the relation proposed by Dolatshahi et al [24] albeit for Unreinforced Masonry (URM) walls are also presented which is a simple circle with these normalized parameters. The results obviously show that, URM infill walls benefit from arching action (the blue ellipses in the figure) prior to reaching SME level (the peak in the IP force-displacement curve) compared to URM walls.…”
Section: Results Discussionmentioning
confidence: 99%
“…It was shown that regardless of the aspect ratio and existence of vertical loads, the OP behavior of infilled frames is not noticeably affected by the IP displacement demand, provided that the displacement is smaller than the displacement related to IP ultimate strength. Unlike the unreinforced masonry walls in which they experience considerable reduction in the OP strength capacity even by applying a small IP displacement [24,25], masonry infill walls benefit from the positive effects of formation of IP diagonal compressive struts in improving the arching action as well as in increasing their OP strength capacity. This is an interesting finding in this study since it clearly proves that the IP and OP interaction for masonry infilled frames may not be much of concern and therefore, the available relations in the design codes for determination of the IP and OP strength capacity of infilled frames as independent behaviors can lead to accurate results.…”
Section: Discussionmentioning
confidence: 99%